Botticelli’s Minerva and the Centaur: Artistic and Metaphysical Conceits - Cheney, Liana De Girolami (Cultural and religious studies, 2020)
Botticelli’s Minerva and the Centaur of 1482-1483, along with his other mythological paintings, the Primavera, the Birth of Venus, and Mars and Venus, remains an iconographical mystery. As such, it is particularly interesting to analyze them. Now at the Galleria degli Uffizi in Florence and National Gallery in London, these paintings, executed between 1480 and 1490, were commissioned with specific aesthetic and intellectual aims and were intended to be hung in private rooms for personal viewing. Botticelli’s mythological paintings reflect the Renaissance humanistic body of thought: the study of antiquity and Neoplatonic philosophy. This essay focuses on one aspect: an interpretation of the influence of antiquity and humanism in Botticelli’s Minerva and the Centaur, a conflation of Minerva pacifica and Minerva pudica.